Mozambique Cell Phone Savings Project: Baseline Survey - International Food Policy Research Institute; Associacao Nutricao Serguranca Alimentar de Mozambique (International Food Policy Research Institute, 2016)
Smallholder households in rural Mozambique are typically characterized by low agricultural productivity, which is in part caused by very low levels of usage of inputs. In the study area, in four districts of Nampula province, farmers are generally far from towns where agricultural input providers are based and formal banking services are available. In absence of these services, smallholders typically face liquidity constraints during the planting season when returns to input usage are the highest. In order to explore potential policy solutions to this challenge, the project combines training and incentives to use mobile money technology alongside targeted input marketing visits to promote formal saving strategies and increase take-up of basic inputs, primarily seeds and fertilizer. The goal of the pilot project was to determine whether combining group-level trainings in mobile money technology with targeted direct marketing could increase input usage, and consequently boost agricultural productivity. In collaboration with Vodacom, IFPRI organized a series of trainings, first at the individual level with farm group leaders carried out in Nampula city in June 2014. This was followed by group trainings at local sites to which all farm group members were invited in July-August 2014. Sampled households (irrespective of whether a member attended training) were then interviewed in August-September 2014. Input marketing visits were carried out by a local input provider, IKURU from October 2014-January 2015. A follow-up survey was then conducted in October-November 2015.